2022
DOI: 10.1002/cpt.2736
|View full text |Cite
|
Sign up to set email alerts
|

Off‐Label, but on‐Evidence? A Review of the Level of Evidence for Pediatric Pharmacotherapy

Abstract: This study shows that the level of evidence for off-label pediatric pharmacotherapy is low: for only 14% of off-label records, high quality studies are available. Thirty-seven percent of offlabel records are not supported by any clinical studies at all. HOW MIGHT THIS CHANGE CLINICAL PHARMA COLOGY OR TRANSLATIONAL SCIENCE? Performing high quality randomized controlled trials for the > 2,000 off-label record is a very long pathway to close this information gap. Alternatively, modeling and simulation may be val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 37 publications
2
18
0
1
Order By: Relevance
“…As stated before, the level of evidence for efficacy has been assessed for all drug dosing recommendations in the European Pediatric Formularies. This information, together with information from a literature search on available pediatric PK data, can be used to identify which dosing recommendations can be supported by PBPK modeling [4]. C. Quality of the compound model is a relevant factor to take into consideration when employing the pragmatic approach (see Sect.…”
Section: Moving Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated before, the level of evidence for efficacy has been assessed for all drug dosing recommendations in the European Pediatric Formularies. This information, together with information from a literature search on available pediatric PK data, can be used to identify which dosing recommendations can be supported by PBPK modeling [4]. C. Quality of the compound model is a relevant factor to take into consideration when employing the pragmatic approach (see Sect.…”
Section: Moving Forwardmentioning
confidence: 99%
“…Knowledge-based dosing guidelines of the DPF are established based on a careful screening of scientific literature. An analysis of the level of evidence showed that one-third of all dosing recommendations in the DPF is backed by only a low level of evidence (i.e., based on comparative research, non-comparative research or expert consensus) [4].…”
Section: Introductionmentioning
confidence: 99%
“…The preferred and often most efficient treatment modality in these age groups is a combination of psychotherapy and psychopharmacology, depending on the nature of the symptoms [ 83 ]. While this holds for the pediatric population in general, children and adolescents treated for cancer often suffer from acute and severe manifestations, especially anxiety-related disorders for which immediate interventions are warranted.…”
Section: Clinical Questionsmentioning
confidence: 99%
“…On the contrary, the lack of labeling for a specific disorder, symptom, age group, or dosage does not automatically mean that the use of the drug is inappropriate for that particular use. Instead, it suggests that the inclusion of a specific drug on the label has not been approved by the EMA and/or FDA [ 82 , 83 , 84 , 85 ]. Thus, the responsibilities for the prescription of that therapy rely on the prescriber only.…”
Section: Recommendations and Critical Issuesmentioning
confidence: 99%
“…Off-label use constitutes the prescription of a drug outside the prescribing information authorized in the drug label or package insert, including indication, age, dose, formulation, or administration route ( COMMITTEE ON DRUGSNeville et al, 2014 ). Studies have found that 42%–73% of drug prescriptions in patients under 18 years were off-label, with the highest frequencies reported in neonates ( Cuzzolin and Agostino, 2016 ; Hoon et al, 2019 ; Yackey et al, 2019 ; van der Zanden et al, 2022 ). However, off-label use does not mean off-evidence nor does it imply improper or contradicted use ( COMMITTEE ON DRUGSNeville et al, 2014 ; Czaja et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%